A Study on Cost Economics of Incorporation of Moringa oleifera on Growth Performance in Nellore Lambs (Indian Journal of Animal Production and Management, 2024)
Sheep is one of the important livestock  species which make a valuable contribution to the  livelihood of the economically weaker sections of  the society by providing income and nutritional  security. Moringa oleifera is one of the potential tree  forages which can be used as livestock feed due to  its faster growth and higher nutritional attributes.  The present study was conducted on 18 post  weaned Nellore lambs of 3 months old having  similar body weights, divided into three groups with  6 lambs in each group for a period of 90 days to  study the effect of Moringa oleifera leaf meal  (MOLM) as a protein supplement on growth  performance and to evaluate the cost economics.  T0, T1 and T2 are the experimental diets having  MOLM at 0,15 and 30 per cent conventional protein  replacement levels. The cost of feed per kg body  weight gain in growing Nellore lambs fed with  experimental diets was Rs.131.34, 111.15 and  105.44, respectively for T0, T1 and T2 diets. The total  cost and cost of production per one kg of meat was  lower in T1 and T2 group lambs which received  concentrate mixture containing MOLM than control  group lambs. Hence, it is recommended that MOLM  can be a cheaper substitute for conventional protein  supplements up to 30% level in the diets of growing  Nellore lambs.
Keywords: Moringa oleifera; cost economics; Nellore lambs